Food Insecurity Among Older Adults with a History of Incarceration. (May 2023) - Jordan, Tamara; Sneed, Rodlescia
We examined the association between history of incarceration (HOI) and food insecurity (FI) among older adults using pooled data from 12, 702 respondents aged 51+ who participated in the 2012 and 2014 waves of the Health and Retirement Study. In our sample, 12.8% of participants reported FI. Those with a HOI had an increased odds of FI (OR 1.83; 95% CI 1.52–2.21). Race/ethnicity moderated the association between HOI and FI. The positive and statistically significant association was concentrated among Non-Hispanic Black and Non-Hispanic White participants. No statistically significant association was found among Hispanic participants or among those from other racial/ethnic groups. Income, depressive symptoms, and functional limitations mediated the association between HOI and FI, with the largest indirect effects observed for income. FI is an important issue among older adults with a HOI. Programs and policy initiatives to increase food access and/or improve earnings in this population may be needed.